Histamine fish poisoning: a common but frequently misdiagnosed condition. Issue 5 (1st September 2002) - Attaran, R R; Probst, F
Abstract : Scombrotoxic or histamine fish poisoning is a common condition normally associated with consuming spoiled tuna, mackerel, bonito, or skipjack. Typical symptoms like flushing, urticaria, and palpitations mimic those of allergy so histamine fish poisoning can easily be misdiagnosed. Diagnosis is often clinical and the mainstay of treatment is antihistamines.